Krivulje preživetja - Stare, Janez (Medicinski razgledi, 2001)
Survival curves are used to describe the proportion of subjects alive through time. Since some of the data on survival are usually censored, special methodsare needed to estimate the survival proportion. In this paper the commonly used method of Kaplan and Meier is described. For better understanding, the connection between the survival curves and the histogram isexplained.
Keywords: Survival analysis; Življenjske tablice; Life tables; Analiza preživetja; Leukemia; Levkemija; Mortality; Preživetje; Survival rate; zdravstvena statistika; krivulja preživetja